Efficacy of therapeutic intervention with NanoBEO to manage agitation and pain in patients suffering from severe dementia: a pilot clinical trial - Scuteri, Damiana; Pagliaro, Martina; Mantia, Isabel; Contrada, Marianna; Pignolo, Loris; Tonin, Paolo; Nicotera, Pierluigi; Bagetta, Giacinto; Corasaniti, Maria Tiziana; , the Pilot BRAINAID Trial investigators (Frontiers in Pharmacology, 2024)
Background: An estimated 57.4 million people live with dementia worldwide, with the social burden of the disease steadily growing. Despite the approval of lecanemab and ongoing trials, there is still a lack of effective and safe treatments for behavioral and psychological symptoms of dementia (BPSD), which affect 99% of patients. Agitation is one of the most disabling BPSD, with a cross-sectional prevalence of ≥50% in nursing homes, and refers to help-seeking behavior in response to various sources of discomfort, among which pain is a crucial component. Methods: This pilot phase of the BRAINAID (NCT04321889) trial aimed to assess the effectiveness of the patented nanotechnological device NanoBEO in older (≥ 65 years) people with severe dementia. This randomized placebocontrolled trial, with quadruple masking that involved all operators and participants, followed the SPIRIT and CONSORT statements. A total of 29 patients completed the trial. The patients were randomly allocated in a 1:1 ratio to the NanoBEO or placebo group, and the corresponding product was applied on both arms once daily for four weeks, with a 4-week follow-up period. The primary endpoint was efficacy against agitation. The secondary endpoints were efficacy against agitation at follow-up and efficacy against pain. Any adverse events were reported, and biochemical analyses were performed. Results: The NanoBEO intervention reduced the frequency (28%) and level of disruptiveness of agitated behaviors. The effect on frequency was statistically significant after two weeks of treatment. The efficacy of NanoBEO on agitated behaviors lasted for the entire 4-week treatment period. No additional psychotropic drugs were prescribed throughout the study duration. The results after one week of treatment demonstrated that NanoBEO had statistically significant analgesic efficacy (45.46% improvement in pain intensity). The treatment was well tolerated. Discussion: This trial investigated efficacy of NanoBEO therapy in managing agitation and pain in dementia. No need for rescue medications was recorded, strengthening efficacy of NanoBEO in prolonged therapy for advanced-stage dementia and the usefulness of the intervention in the deprescription of potentially harmful drugs. This study provided a robust rationale for the application of NanoBEO in subsequent large-scale pivotal trial to allow clinical translation of the product.